2014
DOI: 10.1093/eurheartj/ehu016
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of masked uncontrolled hypertension in people with treated hypertension

Abstract: The prevalence of masked suboptimal BP control in patients with treated and well-controlled clinic BP is high. Clinic BP monitoring alone is thus inadequate to optimize BP control because many patients have an elevated nocturnal BP. These findings suggest that ABPM should become more routine to confirm BP control, especially in higher risk groups and/or those with borderline control of clinic BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
133
4
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 32 publications
19
133
4
18
Order By: Relevance
“…Although echocardiography and PWV measurements were available in most ABPM participants, they were not necessarily obtained concurrently, and the sequence of ABPM and these measures was not uniform across all participants; this further limits our ability to assess causality. We did not distinguish between masked hypertension and masked uncontrolled hypertension, although .90% of participants received antihypertensive medications (45). Additionally, the outcomes assessed in this paper, although clearly important, are still surrogates for clinical cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…Although echocardiography and PWV measurements were available in most ABPM participants, they were not necessarily obtained concurrently, and the sequence of ABPM and these measures was not uniform across all participants; this further limits our ability to assess causality. We did not distinguish between masked hypertension and masked uncontrolled hypertension, although .90% of participants received antihypertensive medications (45). Additionally, the outcomes assessed in this paper, although clearly important, are still surrogates for clinical cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…Albuminuria is expressed as mg/g. in order to assess the appropriateness of nighttime BP control, ABPM performance is required in patients with albuminuria because elevated nighttime BP could be present in patients with an apparently adequate BP control in the office (42).…”
Section: Discussionmentioning
confidence: 99%
“…77 Home BP measurement could be useful in the diagnosis and in the prognostic stratification, also for the nocturnal period, 78 but ABPM seems to be the best method to make an accurate diagnosis. 79,80 In addition, the Ohasama study demonstrated, in a cohort of 843 subjects of the general population who performed ABPM, that the nocturnal BP values were the best predictor of future chronic kidney disease. 81 In the Japan Morning Surge Home Blood Pressure (J-HOP) Study, Kario et al developed a more comfortable device with respect to traditional ABPM device focused on the night time BP values of 02:00, 03:00, 04:00 a.m., which showed in 2562 subjects a strict correlation between nighttime BP values and TOD.…”
Section: Clinical Consequencesmentioning
confidence: 99%